2017
DOI: 10.2147/copd.s149382
|View full text |Cite
|
Sign up to set email alerts
|

Smoking history and emphysema in asthma–COPD overlap

Abstract: BackgroundEmphysema is a distinct feature for classifying COPD, and smoking history (≥10 pack-years) is one of several newly proposed criteria for asthma–COPD overlap (ACO). We studied whether or not a smoking history (≥10 pack-years) and emphysema are useful markers for classifying ACO and differentiating it from asthma with chronic airflow obstruction (CAO).MethodsWe retrospectively studied the mortalities and frequencies of exacerbation in 256 consecutive patients with ACO (161 with emphysema and 95 without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…Se ha evaluado la mortalidad y la frecuencia de exacerbaciones en pacientes con ACO comparado con pacientes con asma y obstrucción al flujo aéreo y pacientes con EPOC (Kurashima et al, 2017). Como resultado, se obtuvo un mejor pronóstico en pacientes con asma y obstrucción al flujo aéreo que en pacientes con ACO y pacientes con EPOC, siendo mejor en pacientes ACO que en pacientes con EPOC.…”
Section: Pronóstico Del Acounclassified
“…Se ha evaluado la mortalidad y la frecuencia de exacerbaciones en pacientes con ACO comparado con pacientes con asma y obstrucción al flujo aéreo y pacientes con EPOC (Kurashima et al, 2017). Como resultado, se obtuvo un mejor pronóstico en pacientes con asma y obstrucción al flujo aéreo que en pacientes con ACO y pacientes con EPOC, siendo mejor en pacientes ACO que en pacientes con EPOC.…”
Section: Pronóstico Del Acounclassified
“…Clinical symptoms can hardly differentiate COPD and asthma bronchial. [1][2][3][4][5][6][7][8] Significant smoking anamnesis can support COPD origin, but some asthma bronchialetic patients are smoker, also. 9 Most of the asthma bronchialetic patients have paroxismatic dyspnoic wheezing in the early morning or after exercise.…”
Section: Introductionmentioning
confidence: 99%
“…9 Most of the asthma bronchialetic patients have paroxismatic dyspnoic wheezing in the early morning or after exercise. [1][2][3][4][5][6][7][8][9] In COPD, the dyspnoea is progressive and it is manifested during exercise at first. Hey fever with obstructive pulmonary disease support the definition of allergic asthma bronchiale bronchiale, but there is a significant portion of COPD patients with hey fever as co-morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] It is one of the most important preventable factors of ill health and death. [ 2 , 3 ] It has been reported that tobacco can increase the incidence of respiratory symptoms and cardiovascular diseases. [ 4 6 ] Specifically, as for men, it can increase the risk of erectile dysfunction.…”
Section: Introductionmentioning
confidence: 99%